2011
DOI: 10.1021/pr200709j
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Characterization of Tupaia belangeri Neuropeptidome Using an Integrated Mass Spectrometric Approach

Abstract: Neuropeptidomics is used to characterize endogenous peptides in the brain of tree shrews (Tupaia belangeri). Tree shrews are small animals similar to rodents in size but close relatives of primates, and are excellent models for brain research. Currently, tree shrews have no complete proteome information available on which direct database search can be allowed for neuropeptide identification. To increase the capability in the identification of neuropeptides in tree shrews, we developed an integrated mass spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 48 publications
0
36
0
Order By: Relevance
“…Our methodological approach utilizes on the integration of data dependent acquisition (DDA) and target-mass list modes, with a mass list based on the previous DDA runs and also on the analysis of peptide rich areas of T. belangeri, i.e. striatum, performed previously [36]. Using this integrated approach, we achieved an identification of 52 peptides from 21 pro-hormone families, including 11 proenkephaline (PENK), 6 Somatostatin (SOM) and three Pro-MCH peptides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our methodological approach utilizes on the integration of data dependent acquisition (DDA) and target-mass list modes, with a mass list based on the previous DDA runs and also on the analysis of peptide rich areas of T. belangeri, i.e. striatum, performed previously [36]. Using this integrated approach, we achieved an identification of 52 peptides from 21 pro-hormone families, including 11 proenkephaline (PENK), 6 Somatostatin (SOM) and three Pro-MCH peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, we used a targeted LC-MS/ MS analysis, with an inclusion list integrated from two independent sources: i) the list of peptides identified in the first step using the DDA approach ii) the previous findings by Petruziziello et al [36] performed on tree shrew striatum (peptide sequence FDR < 1%). The final workflow is shown in the Fig.…”
Section: Lc-ft-ms/ms Data Acquisitionmentioning
confidence: 99%
“…Further comparative analysis shows that our new approach allowed more peptides to be identified than DDA LC-FT-MS/MS analysis combined with the commonly acetic acid solution (AAS) sample treatment method 2,23 or mixing in solution (MIS) multistage extraction method. 10 The results showed that about 82.0% of the peptides identified using method AAS +DDA had sequences identical with those using MOC+CSD. The peptides identified using method MIS+DDA and MOC+DDA had 83.1 and 84.7% sequences identical with those using MOC+CSD, respectively ( Figure 2B).…”
Section: Charge State-directed High Accuracy Tandem Ms Data Acquisitionmentioning
confidence: 94%
“…The main advantage of this approach is that it allows the simultaneous monitoring of many peptides from the same brain tissue derived from a single drug protocol. We used a combination of a robust sample preparation method (18), high accuracy LC-MS analysis (19,20), and the use of multiple synthetic internal standards (21) to compare peptide levels in the DS between chronic nicotine and control animals. Our peptidome analysis determined 14 peptides exhibiting significant changes following chronic nicotine administration.…”
mentioning
confidence: 99%